Смерть у відеоіграх у контексті процесів реміфологізації - Гребенюк, Арсен Вікторович; Гребенюк, Арсений Викторович; Hrebeniuk, Arsen V. (My University, 2016)
Досліджено проблему зображення смерті у відеоіграх у контексті реміфологізації та активізації рудиментів архаїчного мислення в масовій свідомості. Проаналізовано репрезентації життя та смерті в інтерактивному віртуальному світі, їхні особливості й основні різновиди. Розглянуто моральний аспект зображення смерті в інтерактивних творах, їх емоційну складову частину. Обґрунтовано важливе значення відеоігор для досліджень специфіки сучасного неоміфологічного світогляду. The article examines the problem of the image of death in videogames in the context of remythologization processes, activization of archaic thinking rudiments. We consider the close relationship of the videogames phenomenon with concepts such as ritual, magic, soul, embodiment. Author analyzes the representation of life and death in an interactive world, their characteristics and the main varieties. This article touches the moral aspect of the image of death in the interactive works, their emotional components. The article contains brief history of basic concepts of life and death in games. It substantiates the important value of video games for the researches of specifics of the modern neomythological outlook. The position of the author is supported by the authoritative works on mythology, primitive thought and the history of videogames. Narration of the base material is accompanied by examples of the most famous or important games.
Death in Videogames in the Context of Processes of Remythologization
Keywords: міф; реміфологізація; відеогра; архаїчне мислення; масова культура; myth; remythologization; videogame; archaic thinking; mass culture